Identifikasi Bakteri pada Rumput Laut Euchema spinosum yang terserang penyakit Ice-ice di Perairan Pantai Kutuh - Saraswati, Suprabadevi Ayumayasari; Darmasetiyawana, I Made Sena (Journal of Marine and Aquatic Sciences, 2016)
The main causes of ice-ice disease that seaweed production will decline. Bacterial infections occur due to fluctuations in climate change resulted in a decrease in water quality resulting in the durability of seaweed. When seaweed stress will facilitate pathogen infection. Disease pathogens cause damage to internal organs. The spread of bacterial disease in seaweed is generally very fast and can lead to death, so that the loss caused by this disease is quite large. Ice-ice disease occurrence is seasonal and contagious, so the impact on the selling price low. The results showed that there are two types of pathogenic bacteria that can potentially cause disease in which bacteria Vibrio alginoliticus and Pseudomonas aeruginosa. Climate change affects the spatial distribution of micro seaweed bacterial pathogens.
Keywords: Eucheuma spinosum; ice-ice; bacterial pathogens